Chlorinated hydrocarbons in women with repeated miscarriages - Gerhard, Ingrid; Daniel, Volker; Wolf, Sonja; Monga, Bondo; Runnebaum, Benno (Environmental health perspectives, 1998)
This study was conducted to investigate a possible etiological role of chlorinated hydrocarbons in the pathogenesis of repeated miscarriages. The blood levels of chlorinated hydrocarbons [CHCs: pentachlorophenol, hexachlorocyclohexane, hexachlorobenzene, the dichlorodiphenyltrichloroethane (DDT) group, polychlorinated biphenyls] were determined in 89 women with repeated miscarriages, who were referred to the University Hospital of Obstetrics and Gynecology of Heidelberg for investigations between 1989 and 1993, and compared to a previously investigated reference population. In more than 20% of the women, at least one of the CHC levels exceeded the reference range. CHC levels did not differ significantly between women with primary or secondary and early or late miscarriages; neither did they differ between women with hormonal or immunological disorders as causes of repeated miscarriages or women with idiopathic repeated miscarriages. No significant associations were detected between CHC levels and further conceptions or the outcome of further pregnancies. As significant associations were found between increasing CHC blood concentrations and immunological and hormonal changes, CHCs may have an impact on the pregnancy course in certain cases.